Respuesta :

[tex]\left( \cfrac{8}{27}\right)^{ -\frac{2}{3} } =\left( \cfrac{27}{8}\right)^{ \frac{2}{3} } = \sqrt[3]{\left( \cfrac{27}{8}\right)^{2 } } =\sqrt[3]{ \cfrac{729}{64} } =\sqrt[3]{ \cfrac{9^3}{4^3} } = \cfrac{9}{4} [/tex]

True.
remember[tex]x^{-m}=\frac{1}{x^m}[/tex]
and
[tex](\frac{a}{b})^c=\frac{a^c}{b^c}[/tex]
and
[tex]x^\frac{m}{n}=\sqrt[n]{x^m}[/tex]
and
[tex](x^m)^n=x^{mn}[/tex]

so, combining all of those
[tex](\frac{8}{27})^\frac{-2}{3}=\frac{8^\frac{-2}{3}}{27^\frac{-2}{3}}[/tex]=
[tex]\frac{\frac{1}{8^\frac{2}{3}}}{\frac{1}{27^\frac{2}{3}}}=\frac{27^\frac{2}{3}}{8\frac{2}{3}}[/tex]=
[tex]\frac{\sqrt[3]{27^2}}{\sqrt[3]{8^2}}=\frac{\sqrt[3]{(3^3)^2}}{\sqrt[3]{(2^3)^2}}[/tex]=
[tex]\frac{\sqrt[3]{3^6}}{\sqrt[3]{2^6}}=\frac{3^ \frac{6}{3}}{2^ \frac{6}{3}} [/tex]=
[tex]\frac{3^2}{2^2}=\frac{9}{4}[/tex]

true
ACCESS MORE